2018
DOI: 10.1029/2018gl077692
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Rupture and Its Impact on Precipitation in Clean Continental Conditions

Abstract: Pollen grains emitted from vegetation can rupture, releasing subpollen particles (SPPs) as fine atmospheric particulates. Previous laboratory research demonstrates potential for SPPs as efficient cloud condensation nuclei (CCN). We develop the first model of atmospheric pollen grain rupture and implement the mechanism in regional climate model simulations over spring pollen season in the United States with a CCN‐dependent moisture scheme. The source of SPPs (surface or in‐atmosphere) depends on region and some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 58 publications
4
64
0
1
Order By: Relevance
“…Skjøth et al (2007) suggest the deposition of grass pollen is 4 times larger than the 1 cm s −1 estimated for birch pollen, and consistent with the 4.3 cm s −1 measured by Durham (1946) on Secale (rye). We will assume that each pollen particle is 35 µm in diameter, spherical and has a density of 1000 kg m −3 , which is consistent with values used by Melbourne-based researchers (de Morton et al, 2011;Knox, 1993), and similar to the grass pollen density used in Zhang et al (2014). A 35 µm particle with a density of 1000 kg m −3 yields a deposition velocity of 4.6 cm s −1 , which is similar to Skjøth et al (2013).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Skjøth et al (2007) suggest the deposition of grass pollen is 4 times larger than the 1 cm s −1 estimated for birch pollen, and consistent with the 4.3 cm s −1 measured by Durham (1946) on Secale (rye). We will assume that each pollen particle is 35 µm in diameter, spherical and has a density of 1000 kg m −3 , which is consistent with values used by Melbourne-based researchers (de Morton et al, 2011;Knox, 1993), and similar to the grass pollen density used in Zhang et al (2014). A 35 µm particle with a density of 1000 kg m −3 yields a deposition velocity of 4.6 cm s −1 , which is similar to Skjøth et al (2013).…”
Section: Introductionmentioning
confidence: 61%
“…Recently human exposure to pollen has become a focus, particularly in the Northern Hemisphere (e.g. Sofiev et al, 2015;Zhang et al, 2014) and urban areas (Skjøth et al, 2013), such that detailed vegetation taxa maps are being produced for pollen forecasting .…”
Section: Introductionmentioning
confidence: 99%
“…Tiny bio-aerosols (about 1 μm diameter or less) containing Bet v1 antigens 1 have been found in the ambient atmosphere likely due to birch pollen grain rupture (Rantio-Lehtimäki et al 1994;Puc et al 2016). Several researchers (Schappi et al 1997;Chathurika et al 2017;Wozniak et al 2018) found that in light rain conditions, tree pollen grain releases antigens or sub-pollen inner particles contained within the grain into the atmosphere. Lacroix (2005) pointed out that laboratory work made by his team revealed that if pollen is exposed to pollution (O 3 , NO 2 , SO 2 ), an increase of the frequency of rupture, pollen surface cracks, or deformation of the exine is observed which facilitate the release of allergens (Traidl-Hoffmann et al 2003).…”
Section: Impact Of Birch (Betula Spp) Pollen and Its Allergensmentioning
confidence: 99%
“…showed the importance of rain in the release of Bet v1 allergen from the birch pollen grain. Overall, three specific factors are favorable to pollen rupture and release of tiny bio-aerosols: high relative humidity (Miguel et al 2006;Zhou 2014) or rain (Schappi et al 1997;Chathurika et al 2017;Wozniak et al 2018), presence of pollution (Lacroix 2005), and the presence of enhanced atmospheric electrical field (Vaidyanathan et al 2006). These factors can work in synergy and can occur in the atmosphere under various conditions.…”
Section: Impact Of Birch (Betula Spp) Pollen and Its Allergensmentioning
confidence: 99%
“…The process of re-entrainment of pollen grains once they are deposited to the ground is not considered, nor is the rupturing process that releases the allergenic contents of the grains -present on small starch particles. Whilst the impacts of pollen rupturing on numbers of cloud condensation nuclei has been investigated by Wozniak et al (2018), ruptured pollen grains are not routinely monitored in Victoria.…”
Section: Introductionmentioning
confidence: 99%